Diagnostic efficacy of serum presepsin for postoperative infectious complications: a meta-analysis - Lu, Chun-Ying; Kao, Chia-Li; Hung, Kuo-Chuan; Wu, Jheng-Yan; Hsu, Hui-Chen; Yu, Chia-Hung; Chang, Wei-Ting; Feng, Ping-Hsun; Chen, I-Wen (Frontiers in Immunology, 2023)
Background: Postoperative infectious complications (PICs) are major concerns.Early and accurate diagnosis is critical for timely treatment and improved outcomes.Presepsin is an emerging biomarker for bacterial infections. However, its diagnostic efficacy for PICs across surgical specialties remains unclear.In this study, a systematic search on MEDLINE, Embase, Google Scholar, and Cochrane Library was performed on September 30, 2023, to identify studies that evaluated presepsin for diagnosing PICs. PIC is defined as the development of surgical site infection or remote infection. Pooled sensitivity, specificity, and hierarchical summary receiver operating characteristic (HSROC) curves were calculated. The primary outcome was the assessment of the efficacy of presepsin for PIC diagnosis, and the secondary outcome was the investigation of the reliability of procalcitonin or C-reactive protein (CRP) in the diagnosis of PICs.Results: This meta-analysis included eight studies (n = 984) and revealed that the pooled sensitivity and specificity of presepsin for PIC diagnosis were 76% (95% confidence interval [CI] 68%-82%) and 83% (95% CI 75%-89%), respectively. The HSROC curve yielded an area under the curve (AUC) of 0.77 (95% CI 0.73-0.81).Analysis of six studies on procalcitonin showed a combined sensitivity of 78% and specificity of 77%, with an AUC of 0.83 derived from the HSROC. Meanwhile, data from five studies on CRP indicated pooled sensitivity of 84% and specificity of 79%, with the HSROC curve yielding an AUC of 0.89.Presepsin exhibits moderate diagnostic accuracy for PIC across surgical disciplines. Based on the HSROC-derived AUC, CRP has the highest diagnostic efficacy for PICs, followed by procalcitonin and presepsin. Nonetheless, presepsin demonstrated greater specificity than the other biomarkers. Further study is warranted to validate the utility of and optimize the cutoff values for presepsin.